Koinōnia in the Symposium: from community to communion? - Lenner, Zdenek (Pontificia Universidad Católica del Perú. Departamento de Humanidades, 2022)
Plato’s Symposium stages a playful subversion of paiderastia by philosophia through successive interconnected speeches. Phaedrus and Agathon praise Erōs as a god presiding over homoerotic relationships, be it at war or at peace. Pausanias and Eryximachus distinguish between two Erōtes, being eager to supervise these paiderastic communities or even the cosmic harmony. But Aristophanes subverts their perspective by introducing the Androgyne, a combination of male and female, which being displayed by Socrates-Diotima will finally give birth to the Erōs-Daimōn. Only he ensures us real human community by enabling true communion with the divine, witness Alcibiades’ final praise of Socrates.

El Banquete de Platón escenifica una subversión lúdica de la paiderastía por parte de la philosophía a través de sucesivos discursos interconectados. Fedro y Agatón elogian a Érōs como un dios que preside las relaciones homoeróticas, ya sea en la guerra o en la paz. Pausanias y Erixímaco distinguen entre dos Érōtes, ansiosos por supervisar estas comunidades pederásticas e incluso la armonía cósmica. Pero Aristófanes subvierte su perspectiva al introducir al Andrógino, una combinación de hombre y mujer, el cual, siendo expuesto por Sócrates-Diotima, dará finalmente a luz al Érōs-Daímōn. Solo él nos asegurará una verdadera comunidad humana al permitirnos una verdadera comunión con lo divino, como atestigua el elogio final de Alcibíades a Sócrates.
Keywords: Erōs; Philia; Koinōnia; Paiderastia; Philosophia; Érōs; Philía; Koinōnía; Pederastía; Philosophía; https://purl.org/pe-repo/ocde/ford#6.03.01